Evaluation of 11-dehydro-thromboxane B2 as a biomarker of severity and putative therapeutic target in human acute heart failure and cardiogenic shock - Ana Isabel Sousa Oliveira (2022)
Background: The urinary thromboxane A2 metabolite 11-dehydro-thromboxane B2 (U-11dhTXB2) has been associated with cardiovascular morbidity and mortality, but remains scarcely explored in acute heart failure (AHF) and cardiogenic shock (CS). We evaluated U-11dhTXB2 profile in AHF and CS patients, as well as its relationship with isoprostanes, inflammation and platelet activation. The influence of low-dose aspirin was also analysed. Methods: Blood and spot urine samples were collected at admission, days 3-4 and 5-8 in AHF (n=23) and CS (n=25) patients and once in controls (n=22). U-11dhTXB2, urinary isoprostanes and serum proinflammatory/anti-inflammatory cytokines were quantified by immunoassays. Routine laboratory markers and outcomes were also evaluated. Results: At admission, U-11dhTXB2 values were higher in AHF and CS patients (P=0.034), increasing in line with disease severity (P for linear trend =0.015). Admission urinary isoprostanes also increased in AHF and CS patients (P<0.01 vs controls). During hospitalization, U-11dhTXB2 remained unchanged in AHF and CS while isoprostanes even increased in CS (P<0.05 vs admission). Aspirin treatment was associated with lower U-11dhTXB2 values, but not isoprostanes, in both patient groups. U-11dhTXB2 positively correlated with isoprostanes in both AHF and CS and with inflammation and intensive care unit length of stay only in CS. Isoprostanes positively correlated with mean platelet volume only in CS. Conclusions: U-11dhTXB2 increases across AHF spectrum, being significantly correlated with isoprostanes. U-11dhTXB2 relationship with inflammation only in CS suggests its extra-platelet production via cyclooxygenase-2. Low-dose aspirin inhibits U-11dhTXB2 but not isoprostanes, which may contribute to the adverse effects of thromboxane receptor activation.